Foetal pain and anaesthesia during prenatal surgery - Carlo V Bellieni (IMR Press, 2022)
Objectives: Foetal surgery is a relatively new branch of medicine; the health providers involved are currently wondering what kind of anaesthesia should be provided to the foetuses. In the last few years, new advances have been reported on foetal sensoriality and capability for feeling pain; meanwhile alerts have been issued on the risks of prolonged anaesthesia in the early infancy. Aim of this paper is reviewing the main data on foetal pain, to be aware of which is the time in pregnancy when it is likely to be felt. The secondary aim is to point out which are the anaesthetics and analgesics appropriate for prenatal surgery. Mechanism: A review of the literature published in the last 20 years in the field of fetal sensoriality and fetal sergery has been carried out; the most pertinent papers have been retrieved, and their conclusions are here summarized and analysed. Findings in brief: Pain can be felt by the human fetus in the second half of pregnancy: data of physiological and behavioural studies show it with increasing evidence, as long as the gestational age increases. With regard to the best anaesthesia in this case, it seems that the mere anaesthetics given to the mother, though apparently sufficient during laparoscopic surgery, are not sufficient to anesthetize the foetus during open surgery; here some references are given for the best and safest foetal direct analgesic treatment. Conclusions: Surgeons should approach carefully fetal surgery, according with the latest findings in this field.